Feasibility and Effectiveness of E-Test Through Vinesa to Improve Statistical Reasoning Ability Central Tendency Material - Setyaedhi, Hari Sugiharto (Indonesian Journal of Educational Research and Review, 2024)
Lecturers are still lacking in developing electronic statistics course tests through Virtual Learning Unesa (Vinesa), which causes student learning outcomes to decline. The aim of this study was to test the feasibility and effectiveness of electronic central tendency material tests. Data analysis uses quantitative descriptive and t tests. The research subjects were 1 material expert, 1 media expert, 1 language expert, and 28 students. Data collection uses tests, observations, interviews, and questionnaires. The ADDIE model is used in this development research. The feasibility results of material validation, learning media, language, individual and small group trials are each in the very feasible category; the effectiveness results show that the control class (0.45) is in the low category and the experimental class (0.6) is in the sufficient category; and the test results t on sig. (2 tailed) = 0.000 < 0.05. Conclusion The development of electronic tests with central tendency material is suitable for use in tests and is effective in improving students' reasoning abilities. The implication of this research is the development of electronic test products that can be monitored for their level of feasibility, with the aim of improving student reasoning in statistics courses.